Pengaruh Modal Kerja, Kas dan Piutang Terhadap Profitabilitas pada Perusahaan Industri Barang Konsumsi di Bursa Efek Indonesia - Dini Pratiwi; Melia Andayani; Nidyawati Nidyawati; Iskandar Malian; Pahlan Pahlan (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the influence of working capital, cash and receivables on the probability of consumer and industrial goods companies on the Indonesian Stock Exchange. This research uses the cross section method. The results of the t test research show that working capital (X1) against probability (Y) can be processed partially using a calculated t of 1.971≤ -6.5253. Therefore, there is a partially significant influence of working capital on probability. For cash (X2) the probability (Y) t count is -6.64449, while the t count is 1.9721, so it can be concluded that t > t table means that there is a partial significant difference in cash to the probability, at the t count probability of 4.123983 t table is 1.9721. In conclusion, working capital, cash and receivables simultaneously influence probability. Keywords: Cash, Working Capital, Receivables, Profitability